Pengaruh Komitmen Organisasional dan Etika Kerja Islami terhadap Performansi Kerja Para Staf Pengajar pada Perguruan Tinggi di Surakarta dengan Basis Institusi sebagai Variabel Moderator - Wahyudi, Amin (IAIN Salatiga, 2012)
The purposes of this study are: (1) examine the impact of organizationalcommitment to job performance of faculty member in Surakarta; (2) examine the impact of Islamic work ethic to job performance; and (3) examine the moderation role of institutional-base on the impact of Islamic work ethic to job performance. The results show that organizational commitment and Islamic work ethic had significance effect to job performance, but institutional-based had no moderating role in the effect of Islamic work ethic to job performance